Synthesis, characterization and toxicity assessment of chlorantraniliprole nanoemulsion against Helicoverpa armigera - Geeta Devi; Lomash Kumar; Rahul Kumar Dhaka; Karuna Jain; Rahul Saini; Shubham Saini; Anil Jakhar; Sushil Ahlawat; Mehdi Rahimi (Scientific Reports)
Abstract Helicoverpa armigera is a highly devastating and polyphagous pest attacking on different field crops. Effective management of this pest is essential for sustainable agriculture. While traditional chemical pesticides are widely used for their immediate results and ease of application, nanoemulsions offer a promising alternative, paving the way for advanced, efficient pesticide formulations.The current research aimed to develop oil-in-water (O/W) chlorantraniliprole stable nanoemulsion using combinations of different solvents (butanol, dimethyl sulfoxide and toluene), tween- 80 (non-ionic surfactant) and sodium laurel sulfonate (anionic co-surfactant) to reduce the dose and increase toxicity of chlorantraniliprole as targeted pesticide. Ultrasonication, a high energy emulsification method, is adopted to obtain the particle size in nanometre (nm). The nano size of emulsion is confirmed by Dynamic light scattering (62.43 nm), Scanning electron microscopy (55 ± 5 nm), X-ray diffraction (42.9 nm), and Transmission electron microscopy (22.5 ± 2.5 nm), Stability of synthesized nanoemulsion is confirmed via, centrifugation, freeze thaw cycle, heating cooling test, and zeta potential. Moreover, the toxicity of chlorantraniliprole nanoformulations is evaluated against H. armigera and compared with commercially available chlorantraniliprole formulation (18.5 SC). Chlorantraniliprole nanoemulsion formulation is 3.3 times more toxic than commercial formulation using topical application method (3rd instar larvae) and 2.2 times more toxic than commercial formulation using diet incorporation method (1st instar larvae). Consequently, this cutting-edge research holds great potential for revolutionizing targeted pesticide delivery systems, paving the way for more effective and precise pest management in agriculture.